Joint attention communication and other minds : issues in philosophy and psychology - Eilan, Naomi (Oxford : Clarendon Press ; New York : Oxford University Press, 2005)
"This book contains research into the cognitive phenomenon of 'joint attention'. Philosophical and psychological perspectives on the nature and significance of this phenomenon are examined"--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2023. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Joint attention; Electronic books